Sustainability Committee Moderating Firm Value, Profitability, and Board Characteristics on Carbon Disclosure - Suciati, Suciati; Wahyuningrum, Indah Fajarini Sri (Universitas Syiah Kuala, 2025)
The purpose of this study is to examine the influence of firm value, profitability, board size, and board gender diversity on carbon emissions disclosure, as well as to determine whether sustainability committees act as moderating variables in these relationships. This quantitative study analyzes panel data from 55 energy sector companies listed on the Indonesia Stock Exchange with a five-year research period (2019-2023) selected through purposive sampling. The analysis technique employs Moderated Regression Analysis (MRA) with a fixed-effects model and the Driscoll-Kraay standard error, as implemented in STATA 19. The results indicate that firm value has a significant positive effect on carbon emissions disclosure, while profitability, board size, and board gender diversity do not affect carbon emissions disclosure. The sustainability committee does not moderate the relationship between the independent variables and carbon emissions disclosure. This study adopts two innovative approaches, namely positioning the sustainability committee as a moderating variable, which has been minimally explored in previous literature, and applying corporate value as an independent predictor, which is generally treated as a dependent variable in previous studies